An evaluation of a bioelectrical impedance analyser for the estimation of body fat content. Issue 1 (March 1993) - Maughan, R J
Abstract : Measurement of body composition is an important part of any assessment of health or fitness. Hydrostatic weighing is generally accepted as the most reliable method for the measurement of body fat content, but is inconvenient. Electrical impedance analysers have recently been proposed as an alternative to the measurement of skinfold thickness. Both these latter methods are convenient, but give values based on estimates obtained from population studies. This study compared values of body fat content obtained by hydrostatic weighing, skinfold thickness measurement and electrical impedance on 50 (28 women, 22 men) healthy volunteers. Mean(s.e.m.) values obtained by the three methods were: hydrostatic weighing, 20.5(1.2)%; skinfold thickness, 21.8(1.0)%; impedance, 20.8(0.9)%. The results indicate that the correlation between the skinfold method and hydrostatic weighing (0.931) is somewhat higher than that between the impedance method and hydrostatic weighing (0.830). This is, perhaps, not surprising given the fact that the impedance method is based on an estimate of total body water which is then used to calculate body fat content. The skinfold method gives an estimate of body density, and the assumptions involved in the conversion from body density to body fat content are the same for both methods.